OH, THOSE BABY BLUES: When you are dealing with a child with PHPV - Atwell, Dawn (Operating Room Nurses Association of Canada Journal, 2003)
In 1995 a mother had concerns about her infant son. She thought she could see a white, crescent moon shape in the upper medial aspect of his left eye. This shape could only be seen when the lights were low and the pupils were dilated. Unfortunately, no one else could see it. She also noticed that her son behaved as if he could not see if she covered his right eye. Instinct told this mother to get answers to her questions. Her family doctor referred her to an ophthalmologist. The ophthalmologist examined the left eye and told the mom that her son has PHPV.